2008
DOI: 10.1189/jlb.0408249
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive biomarker monitoring in cytokine therapy: heterogeneous, time-dependent, and persisting immune effects of interleukin-10 application in psoriasis

Abstract: Cytokine and anticytokine treatments represent promising approaches for therapy of immune-mediated diseases. In humans, however, regulatory consequences of interference with the cytokine network are only partially understood. Biomarker analysis in clinical studies may help to overcome this complexity and provide novel information about the in vivo relevance of individual cytokines. We report systemic immunological effects of IL-10 therapy in 10 psoriasis patients during a 7-week treatment period followed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 71 publications
(74 reference statements)
1
22
0
Order By: Relevance
“…68 In our study, patients had serum concentrations of IL-10 similar to those described in previous works. 61,69 Itolizumab treatment did not have a clear effect on IL-10 modulation. Nevertheless, increased serum levels were observed at the end of the scheme, likely because higher itolizumab dose was administered during the entire schedule.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…68 In our study, patients had serum concentrations of IL-10 similar to those described in previous works. 61,69 Itolizumab treatment did not have a clear effect on IL-10 modulation. Nevertheless, increased serum levels were observed at the end of the scheme, likely because higher itolizumab dose was administered during the entire schedule.…”
Section: Discussionmentioning
confidence: 86%
“…60 IL-10 inhibits pro-inflammatory cytokine production by activated T lymphocytes, but treatment of psoriasis patients with recombinant human IL-10 failed to induce an overall anti-inflammatory response. 61 The expression levels of this cytokine in the lesions and the changes in different therapeutic studies do not show a regular pattern. In a study where human recombinant IL-11, a Th2 cytokine, was administered, 62 low levels of IL-10 were observed and, as seen upon itolizumab therapy, TNF and IFN-γ levels were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This allows us to learn from the potential failure of drugs and to re-adapt attempts aiming to modulate the immune system more precisely [14] . Furthermore, monitoring of immunological mediators is important also for safety reasons and for the understanding/ interpretation of side effects [15] . In order to achieve a more complete picture in order to allow an adequate interpretation of data, several multiplex analysis platforms have been developed, which allow the parallel analysis of multiple analytes from small amounts of material.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, human skin mast cells have been found to be major producers of the IL-10 homolog IL-22 in psoriasis patients, leading to increased psoriatic plaques (42). One clinical study found that IL-10 therapy in psoriasis patients exacerbated inflammation and increased Th2 cytokines (9). While miR-155 expression was found to be lower among benign skin disorders (including psoriasis) than in cutaneous T cell lymphoma (43), no comparison of miR-155 expression in healthy and psoriatic skin has been published.…”
Section: Discussionmentioning
confidence: 99%
“…However, animal studies and clinical administration of IL-10 disclosed undesirable pro-inflammatory properties. Several studies of IL-10 administration in experimental endotoxemia (6) as well as studies of patients with Crohn’s disease (7), systemic lupus erythematosus (SLE) (8), and psoriasis (9) have shown immunostimulatory effects of IL-10 that correlated with disease severity.…”
Section: Introductionmentioning
confidence: 99%